2016
DOI: 10.1007/s13300-016-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Faulty Injection Technique: A Preventable But Often Overlooked Factor in Insulin Allergy

Abstract: Insulin hypersensitivity—a rare occurrence with currently available insulin preparations—may have varied manifestations, ranging from a local injection site allergy to severe generalized anaphylactic reactions. While various additives included in commercial insulin preparations and insulin peptides themselves remain the primary allergens responsible, faulty injection technique may at times potentiate the development of insulin allergy. Management of insulin allergy is complex, potentially dangerous at times, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Incorrect insulin injection techniques are not only associated with higher consumption of insulin and higher glycated hemoglobin values but also are responsible for higher frequencies of unexpected hypoglycemia and glucose variability [ 8 ]. Moreover, it has been also reported that faulty injection technique can cause insulin allergy [ 12 , 13 ]. Furthermore, there are evidences suggesting suboptimal disposal of needle after use [ 8 , 9 ], thereby increasing the risk of transmitting blood-borne infections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incorrect insulin injection techniques are not only associated with higher consumption of insulin and higher glycated hemoglobin values but also are responsible for higher frequencies of unexpected hypoglycemia and glucose variability [ 8 ]. Moreover, it has been also reported that faulty injection technique can cause insulin allergy [ 12 , 13 ]. Furthermore, there are evidences suggesting suboptimal disposal of needle after use [ 8 , 9 ], thereby increasing the risk of transmitting blood-borne infections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these insulin formulations had cresol, she was patch tested negative for cresol. Other insulin-allergy mimics reported are due to allergens in insulin infusion devices ( 20 ), allergy to natural latex rubber antigens in insulin injection material ( 21 ) and faulty injection technique ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correct insulin delivery is critical for better diabetes control [ 5 ]. Faulty injection technique not only results in inadequate glycemic control [ 6 ] but also results in hypoglycemia [ 7 ] and insulin allergy [ 8 , 9 ]. In this study, we report a case of poor glycemic control as a consequence of inappropriate insulin injection technique.…”
Section: Introductionmentioning
confidence: 99%